Critical Success Factors of Digital Transformation in the Higher Education Sector - Asma Aleidi (International Journal of Advanced Science and Computer Applications, 2026)
Digital transformation (DT) has a significant impact on higher education institutions (HEIs), which is directly related to the development and performance improvement. There is, however, lack of understanding of the critical success factors of digital transformation in HEIs. Based on a review of the related literature, the study identified the critical success factors of digital transformation including digital literacy as central to DT process. This identification led to the development of the initial conceptual framework. Such findings can help to develop appropriate strategies and policies for better implementation of digital transformation programs for improving HEIs (managers, academics, and staff) in their DT.